2017
DOI: 10.2217/fmb-2017-0052
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm Activity of Propolis Extract onFusariumSpecies from Onychomycosis

Abstract: Propolis extract can be an alternative topical treatment of onychomycosis caused by Fusarium spp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 23 publications
4
36
0
4
Order By: Relevance
“…In vitro antifungal susceptibility testing of planktonic cells was performed using a microdilution method adapted from Galletti et al (2016) and Clinical and Laboratory Standards Institute [CLSI] (2008) M38-A2 protocol. For this test, the serial dilution was performed at a ratio of two, from 1:2 to 1:1024.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro antifungal susceptibility testing of planktonic cells was performed using a microdilution method adapted from Galletti et al (2016) and Clinical and Laboratory Standards Institute [CLSI] (2008) M38-A2 protocol. For this test, the serial dilution was performed at a ratio of two, from 1:2 to 1:1024.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the results found in this research, propolis extract also showed antibiofilm activity against clinical isolates and ATCC of Fusarium species found in patients with onychomycosis, where it was found that the biomass of the treatments decreased significantly when compared to the control, as well as the number. of viable cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…Propolis is a resin and a natural product with medicinal properties. The production of propolis occurs from the collection of plant structures and its mixture with wax and salivary enzymes, having the modeling function of a varnish, besides protecting and sterilizing the internal and external parts of the hive, keeping the humidity and temperature (4–6).…”
Section: Introductionmentioning
confidence: 99%
“…And, an emerging fungal pathogen that has stood out in terms of its potential for biofilm formation is Fusarium . The incidence of fusariosis has been increased in recent years, and there are many reports in the literature showing onychomycosis and keratitis cases caused by biofilm‐forming fungi 5,6 . When related to keratitis, they originate mainly from eye trauma or the use of contact lenses, whereas in cases of onychomycosis, nail trauma is in evidence 7‐10 …”
Section: Introductionmentioning
confidence: 99%